Pengelolaan Aktivitas Ekstrakurikuler Seni Musik di Pendidikan Anak Usia Dini (PAUD) - Raharjo, Itot Bian; Yulianto, Dema (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2020)
This study provides an overview of the management of the implementation of music extracurricular activities in early childhood education (PAUD). The background is the constraints or problems in the management system. Therefore, the implementation of music extracurricular activities in PAUD must be managed seriously. Good and suitable management of extracurricular music implementation will have a positive effect on the quality of education in PAUD. This research method is literature study. Data collection is by collecting main and supporting reference data. The data analysis technique is content analysis. The results of the assessment on the management of the implementation of music extracurricular activities in early childhood education are carried out using 4 stages, namely: 1) planning needs analysis, types, the background, implementation objectives, materials, evaluation tools, outputs, sarpras, criteria for trainers (instructors), 2) organizing in division of tasks, authorities, and responsibilities for executing extra activities, 3) implementation of activities in accordance with the implementation plan and organizing process, and 4) evaluation of activities. Keyword: management, extracurricular, music art, PAUD.